Ekologi meiobentos dan harpacticoida hutan paya laut Semenanjung Malaysia - Zaleha Kassim (Penerbit UMT, Universiti Malaysia Terengganu, 2009)
A study of aquatic invertebrates in mangrove ecology in Malaysia.